Combination of Periodontal Ligament Stem Cells and Metformin via Organic Cation Transporters for Periodontal Regeneration in Rats - Qingchen Qiao; Zeqing Zhao; Yaxi Sun; Jing Wang; Xiaowei Li; Li Zhang; Hao Yang; Ning Zhang; Ke Zhang; Yuxing Bai (Biomolecules)
Periodontal regeneration remains challenging due to individual variability, especially in treatments involving bioactive factors such as metformin. This study aimed to investigate the role of organic cation transporters (OCTs) in metformin-induced periodontal regeneration. The expression and function of OCTs in human periodontal ligament stem cells (hPDLSCs) were assessed, and OCT-mediated metformin uptake was quantified by high-performance liquid chromatography (HPLC). Osteogenic and cementogenic differentiation markers were analyzed in vitro, and periodontal regeneration was evaluated using a rat periodontal defect model. OCTs were differentially expressed and functional in hPDLSCs. Both the OCT1 inhibitor cimetidine and OCT1 knockdown significantly reduced intracellular metformin accumulation to 50–60% and 20–30% of control levels, respectively (p < 0.01). Cimetidine diminished the osteogenic and cementogenic effects of metformin by approximately 31–48% and 32–40%, respectively (p < 0.01). In vivo, oral administration of cimetidine decreased bone regeneration by 25% and cementum regeneration by 36% compared with controls receiving GelMA/hPDLSCs/metformin (p < 0.01). This study demonstrates that OCTs regulate metformin uptake in hPDLSCs, and that inhibition of OCT1 by cimetidine significantly reduces the osteogenic and cementogenic efficacy of metformin, providing the first evidence of drug interactions affecting periodontal regeneration mediated by OCT transport in rats.